2022
DOI: 10.3390/v14122775
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Mutations Associated with Emergent Variants Can Be Detected as Low-Frequency Mutations in Early SARS-CoV-2 Pandemic Clinical Samples

Abstract: Genetic analysis of intra-host viral populations provides unique insight into pre-emergent mutations that may contribute to the genotype of future variants. Clinical samples positive for SARS-CoV-2 collected in California during the first months of the pandemic were sequenced to define the dynamics of mutation emergence as the virus became established in the state. Deep sequencing of 90 nasopharyngeal samples showed that many mutations associated with the establishment of SARS-CoV-2 globally were present at va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Notably, although H655Y and I1081V appear to be linked, these mutations are not co-located on the spike trimer. Although previous studies have shown that H655Y is frequently detected during passage and in variant genotypes [ 11 , 16 , 32 ], the co-occurrence of I1081V has not been documented. Similarly, mutation I569S was selected for during virus only passage but has not been described in the literature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, although H655Y and I1081V appear to be linked, these mutations are not co-located on the spike trimer. Although previous studies have shown that H655Y is frequently detected during passage and in variant genotypes [ 11 , 16 , 32 ], the co-occurrence of I1081V has not been documented. Similarly, mutation I569S was selected for during virus only passage but has not been described in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…Variants were called using Mappgene, ( https://github.com/LLNL/mappgene ) a SARS-CoV-2 variant calling pipeline for high performance computing environments (HPC) [ 16 ]. Mappgene employs BWA-MEM [ 17 ] for read alignment, iVar 1.3.1 for read trimming/filtering/variant calling, and LoFreq v2.1.5 to call variants [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Notably, although H655Y and I1081V appear to be linked, these mutations are not co-located on the spike trimer. Although previous studies have shown that H655Y is frequently detected during passage and in variant genotypes (11,16,32), the co-occurrence of I1081V has not been documented. Similarly, mutation I569S was selected for during virus only passage but has not been described in the literature.…”
Section: De Novo Mutations In Rbdmentioning
confidence: 87%
“…2.9 Bioinformatic analysis. Variants were called using Mappgene, (https://github.com/LLNL/mappgene) a SARS-CoV-2 variant calling pipeline for high performance computing environments (HPC) (16). Mappgene employs BWA-MEM (17) for read alignment, iVar 1.3.1 for read trimming/filtering/variant calling, and LoFreq v2.1.5 to call variants (18).…”
Section: Neutralization Assaymentioning
confidence: 99%